PENGARUH STATUS SOSIAL EKONOMI DAN PENGALAMAN BELAJAR TERHADAP MINAT PASCASARJANA MAHASISWA PENDIDIKAN EKONOMI - Nilakandi, Andri Koko Perdana; Witarsa, Witarsa; Syahrudin, Husni (Universitas Tanjungpura, 2025)
The purpose of this study was to determine the effect of family socioeconomic status and learning experience on interest in continuing postgraduate studies. The type of research used is Ex Post Facto research, which is a type of quantitative research conducted after the event or independent variable being studied occurs. The population inthe study were economics education students from the 2020-2023 intake. The number of samples in this study was 111 students with a sampling technique using proportional random sampling. Data collection using questionnaires. Hypothesis testing was carried out using t and F tests and processed with SPSS. The results of the partialt test 1). There is no partial influence between family socioeconomic status (X1) on interest in continuing postgraduate studies (Y) with a sig value of 0.468 0.05; 2). There is a partial influence between learning experience and interest in continuing postgraduate studies (X2) on saving behavior (Y) with a sig value of 0.000 0.05. The results of this study indicate that there is a simultaneous influence of family socioeconomic status and learning experience on the interest in continuing postgraduate studies of 0.419 or 41.9% and the remaining 58.1% is influenced by other factors.